Umrah Backpacker: Studies and Research Path - Maliha, Hasna; Rahayu, Solihah Sari (Halal Tourism and Pilgrimage, 2024)
Backpacker Umrah exemplifies the flexibility, where pilgrims choose economical self-travel—adjusting schedules, transiting between countries for cheap flights, and sharing costs with others. This study aims to see the development of research on the topic "Umrah Backpacker" and research plans that can be carried out based on journals published with this theme. This study uses a qualitative method with a bibliometric analysis approach. The data used is secondary data with the theme "Umrah Backpacker" which comes from the Dimension database with a total of 55 journal articles. Then, the data was processed and analyzed using the VosViewer application with the aim of finding out the blibliometric map of the development of "Umrah Backpacker" research in the world. The results of the study found that there are 3 clusters with the most used words are umrah, home, pilgrim, hajj, knowledge, and Islam. Then, the topics of research paths related to Umrah Backpacker are behavioral, health, and risk factors, diaspora mobility and identity, and experiential religious tourism.